2018
DOI: 10.1080/15548627.2018.1501251
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant retinitis pigmentosa-associated gene PRPF8 is essential for hypoxia-induced mitophagy through regulating ULK1 mRNA splicing

Abstract: Aged and damaged mitochondria can be selectively degraded by specific autophagic elimination, termed mitophagy. Defects in mitophagy have been increasingly linked to several diseases including neurodegenerative diseases, metabolic diseases and other aging-related diseases. However, the molecular mechanisms of mitophagy are not fully understood. Here, we identify PRPF8 (pre-mRNA processing factor 8), a core component of the spliceosome, as an essential mediator in hypoxia-induced mitophagy from an RNAi screen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…In addition, the resistance of mt-Keima to lysosomal degradation causes the integration of the mt-Keima signal, allowing for the easy quantitative measurement of mitophagy activity. These properties have led to the increasing use of mt-Keima to study mitophagy in vitro (13)(14)(15)(16). We previously generated a transgenic mouse that ubiquitously expresses the mt-Keima protein, allowing the first general observation of in vivo mitophagy (17).…”
mentioning
confidence: 99%
“…In addition, the resistance of mt-Keima to lysosomal degradation causes the integration of the mt-Keima signal, allowing for the easy quantitative measurement of mitophagy activity. These properties have led to the increasing use of mt-Keima to study mitophagy in vitro (13)(14)(15)(16). We previously generated a transgenic mouse that ubiquitously expresses the mt-Keima protein, allowing the first general observation of in vivo mitophagy (17).…”
mentioning
confidence: 99%
“…PRPF8 is the core protein of splicing, the mutation of PRPF8 could cause the death of model cell, and it has an important relationship with the occurrence of the disease particularly in cancer [21]. Recent study reported that knockdown of PRPF8 signi cantly impairs mitophagosome formation, thus, these ndings demonstrate that PRPF8 is essential for mitophagy and suggest that dysregulation of spliceosome-mediated mitophagy may contribute to pathogenesis of disease such as cancer [22]. PRPF8 is a highly conserved pre-mRNA splicing factor and a component of spliceosomal small nuclear ribonucleoproteins (snRNPs), which is essential in RNA and mRNA splicing through transesteri cation and spliceosome processes [23].…”
Section: Discussionmentioning
confidence: 99%
“…When mitochondria are damaged, they can be selectively removed by autophagy, called mitophagy. Some genes associated with autosomal dominant RP, including PRPF6, PRPF31, SNRNP200, and PRPF8 (core spliceosomal components) [129][130][131], are suggested to be responsible for ULK1 mRNA mis-splicing (an important protein for mitophagy initiation) and subsequent mitophagy defects [132].…”
Section: Inherited Retinal Dystrophiesmentioning
confidence: 99%